The Effect of Insertion Rate on The Adaptability of Gutta-Percha and The Apical Extrusion of Thermoplasticized Gutta Percha Obturation Techniques. - Al-Shimari, Samer Aun Thyab (Journal of Baghdad College of Dentistry, 2017)
Background: In the Thermafil as a root canal obturation, system little is known about the effect that varying rates of insertion have on the adaptability of thermoplasticized GP and the amount of apical extrusion.Materials and methods: thirty simulated root canals were obturated with thermafil obturators and Apexit Plus sealer at three different insertion rates. The obturated canals were sectioned at three different levels, the sealer average film thickness for each section was calculated and the amount of apical extrusion for each canal was conducted. Results: the higher adaptability was seen with the faster insertion rate while the slower insertion rate showed fewer tendencies to cause apical extrusion. Conclusions: the intermediate insertion rate had the best results between the other two rates for both adaptability and apical extrusion.